Community Satisfaction with Online Transportation in Tegal - Satria, Muhammad Hanif; Saragi, Reza Christian; Perdana, Tegar Putra Adi; Brilianti, Dani F. (Kirana Publisher (KNPub), 2024)
This research aims to increase the level of online transportation customer satisfaction in Tegal, a large city in Indonesia. To achieve this, this research investigates the factors that influence online transportation customer satisfaction. This research uses mixed methods with interview and questionnaire data collection techniques. Valid data test results and research findings show that overall, online transportation users from the people of Tegal City are happy with the services they receive. The things that make customers happy are service quality, service accessibility and availability, and safety and comfort. By analyzing local customer perceptions and expectations, this research provides insight for online transportation companies to improve service quality and better meet the needs of the Tegal community.